2010
DOI: 10.1007/s12603-010-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

How is the risk of undernutrition associated with cardiovascular disease among individuals of advanced age?

Abstract: Two thirds of the study participants had CVD and half were at risk of undernutrition. Nutrition risk was mildly associated with CVD. This study provides further evidence that those in advanced age are at risk of undernutrition. Further research is needed to establish how the causes and consequences of CVD are related to nutrition risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…This finding is confirmed in other studies showing that malnourished residents are more care dependent. Other studies confirm the present findings on the relationship between malnutrition and CVD ( 49 , 50 ) . Furthermore, the remaining confounders found in the GEE analyses have also been indicated by other studies.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is confirmed in other studies showing that malnourished residents are more care dependent. Other studies confirm the present findings on the relationship between malnutrition and CVD ( 49 , 50 ) . Furthermore, the remaining confounders found in the GEE analyses have also been indicated by other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Donini et al . as well as other authors confirmed in their systematic literature review that age‐related decline in stature induces a BMI increase of 1.5 kg/m 2 in men and 2.5 kg/m 2 in women, despite the minimal changes in body weight . In the present study, more than half the participants overestimated their height, with height being over‐reported by 1 ± 3 cm.…”
Section: Discussionsupporting
confidence: 83%
“…CVD was predictive of nutrition risk. in nZ a mild relationship between nutrition risk and CVD in older people has previously been identified (31) and further research is needed to establish the causes. in nZ a mild relationship between nutrition risk and CVD in older people has previously been identified (31) and further research is needed to establish the causes.…”
Section: Discussionmentioning
confidence: 99%